Perspectives on Teacher Professionalism: A Review of Literature - Mai, Duong Thu (VNU Journal of Foreign Studies; Vol 32 No 4, 2016)
Abstract: Teachers, more than any other concerned people, often stand in the centre of the ever on-going debates in advancing education quality. In recent decades, when the need for a professionalization agenda of the teaching job has been made urgent in every education context, teacher professionalism (TP) is among the most frequently mentioned dimension. It is impossible to name any professionalization effort without describing what the corresponding teaching professionals look like. In Vietnam, recent years have also witnessed a rapid increase of studies and attention for teacher’ knowledge and competence while the local literature on this issue is still rather limited. By presenting the existing perspectives of TP along with practical examples before discussing them in the light of major education goals, this article aims to provide a more systematic conceptualization of this construct and its relatives, taking into account the well studied theories and practices by world education researchers, to provide a reference source for concerned policy makers, teacher education curriculum developers, teacher trainers, researchers, and student researchers in education.